Education, judiciary and Constitution, 1978-2018 (I). The single-sex schooling - Viñao Frago, Antonio (Historia y Memoria de la Educación, 2019)
Single sex schooling was one of the five points considered in the court ruling established by the Constitutional Court (CC) on 18 April 2018, in a decision rejecting the appeal presented by over 50 Socialist Party MPs against the Organic Law for the Improvement of Educational Quality of 10 December 2013. A close reading of this ruling reveals the ideological confrontation between the majority view represented by the CC and the dissenting view expressed about whether or not this educational model was discriminatory and whether or not such a model is constitutional. Other elements include a discussion concerning the existence and content of a constitutional educational ideology. In this essay both the ruling and the dissenting votes are commented upon and contextualized.